Molecular phenotype of kidney transplant indication biopsies with inflammation in scarred areas. Issue 5 (13th December 2018) - Halloran, Philip F.; Matas, Arthur; Kasiske, Bertram L.; Madill‐Thomsen, Katelynn S.; Mackova, Martina; Famulski, Konrad S.
Abstract : In kidney transplant biopsies, inflammation in areas of atrophy‐fibrosis (i‐IFTA) is associated with increased risk of failure, presumably because inflammation is evoked by recent parenchymal injury from rejection or other insults, but some cases also have rejection. The present study explored the frequency of rejection in i‐IFTA, by using histology Banff 2015 and a microarray‐based molecular diagnostic system (MMDx). In unselected indication biopsies (108 i‐IFTA, 73 uninflamed IFTA [i0‐IFTA], and 53 no IFTA), i‐IFTA biopsies occurred later, showed more scarring, and had more antibody‐mediated rejection (ABMR) based on histology (28%) and MMDx (45%). T cell–mediated rejection (TCMR) was infrequent in i‐IFTA based on histology (8%) and MMDx (16%). Twelve i‐IFTA biopsies (11%) had molecular TCMR not diagnosed by histology, although 6 were called borderline and almost all had histologic TCMR lesions. The prominent feature of i‐IFTA biopsies was molecular injury (eg, acute kidney injury [AKI] transcripts). In multivariate analysis of biopsies >1 year posttransplant, the strongest associations with graft loss were AKI transcripts and histologic atrophy‐scarring; i‐IFTA was not significant when molecular AKI was included. We conclude that i‐IFTA in indication biopsies reflects recent/ongoing parenchymal injury, often with concomitant ABMR but few with TCMR. Thus, the application of Banff i‐IFTA in the population of late biopsies needs to be reconsidered. Abstract : Molecular analysis of indication kidney transplant biopsies with inflammation in areas of scarring (i‐IFTA) reveals extensive recent or ongoing parenchymal injury, often with concomitant antibody‐mediated rejection, but usually without T cell– mediated rejection, suggesting Banff 2017 terminology classifying such biopsies as chronic active TCMR should be revisited.